Gender and Sovereignty - Hoffman, J. author. aut Link
XI, 228 p.
Keywords: Gender and Sovereignty seeks to reconstruct the notion of sovereignty in post-patriarchal society. Sovereignty is linked to emancipation, and an attempt is made to free both concepts from the static characteristics which derive from the Enlightenment and an uncritical view of the state. To reconstruct sovereignty, we must look beyond the state. Sovereignty, analysed in relational terms, becomes aligned with autonomy and self-determination in a world in which men and women can only be sovereign when they empower one another.